Military antishock trousers. - Kemeny, A.
The military antishock trouser (MAST) is an inflatable garment that surrounds the lower portion of the body (legs and abdomen). It is primarily used as an emergency garment to stop bleeding in the lower extremities, increase peripheral resistance to better perfuse the upper body, and increase blood flow to the brain and other vital organs. The MAST garment consists of three chambers, which can be inflated separately or together with a simple foot pump to 100 mmHg. MAST garments are designed to be applied rapidly in the field, and they use Velcro straps to secure the leg and abdominal chambers on a patient. MAST is most often used for rapid transport of patients with hypovolemia resulting from shock or trauma.
Keywords: Military antishock trousers; Velcro straps; Abdomen; Bleeding; Blood flow; Brain; Emergency garment; Foot pump; Hypovolemia; Inflatable garment; Legs; Lower extremities; Perfusion; Peripheral resistance; Rapid patient transport; Shock; Trauma; Vital organs